612 Incidental discovery of chronic lacunar infarction in the head of the caudate nucleus: pathophysiological considerations and retroactive etiologic diagnosis of a depressive syndrome; case presentation (Balneo and PRM Research Journal, 2024)
Neuroimaging studies demonstrated the complex caudate nucleus' interrelationships within topographically organized cortical networks and its strategic role in emotional balance.The clinical case depicts a 71-year-old female patient with chronic depressive syndrome, orthostatic hypotension, hyperlipidemia, and arthritis. CT cerebral imagery incidentally revealed an old lacunar infarction in the right caudate nucleus with a diameter of about 6 mm.The authors hypothesized that the old lacuna was incriminated as the organic substrate for chronic neuropsychiatric illness in an older woman with risk factors for cerebral small vessel disease.The etiopathological assumption was contextualized in a selective literature review that focused on relevant data from recent publications and emphasized the caudate`s strategic role in emotional balance and dysthymia.Unilateral or bilateral small lacunae in the caudate nuclei are associated with a high risk of developing psychiatric complications but not motor deficits after stroke.Written informed consent was obtained from the patient for the inclusion and use of materials related to the case, respecting the confidentiality of her identity data, and the Bioethical Commission approved the study.Keywords: caudate nucleus; lacunar stroke; incidentaloma; depressive syndrome; case report